2008
DOI: 10.1042/bc20070160
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the small GTPase Rac1 by a specific guanine‐nucleotide‐exchange factor suffices to induce glucose uptake into skeletal‐muscle cells

Abstract: Collectively, Rac1 activation specifically in membrane ruffles by the GEF FLJ00068 is sufficient for insulin induction of glucose uptake into skeletal-muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
140
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(146 citation statements)
references
References 35 publications
5
140
1
Order By: Relevance
“…30) Several studies 7,34) have indicated the involvement of sHsp in the fast-to-slow transition process during skeletal muscle aging. 12,30) In this study, we expected to see an obvious difference in the senescent muscle of chicken, but we found no significant difference in the expression of fast type MHC and the HSF isoforms (Fig. 4(A) and 4(B)).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…30) Several studies 7,34) have indicated the involvement of sHsp in the fast-to-slow transition process during skeletal muscle aging. 12,30) In this study, we expected to see an obvious difference in the senescent muscle of chicken, but we found no significant difference in the expression of fast type MHC and the HSF isoforms (Fig. 4(A) and 4(B)).…”
Section: Discussionmentioning
confidence: 81%
“…11,12) The concentration of purified GST-HSPB1 protein was assayed by BCA protein assay and confirmed with SDS-PAGE and CBB staining.…”
Section: Two-dimensional Gel Electrophoresis (2-de)mentioning
confidence: 99%
“…Despite this apparent independence of the Akt and Rac-1 signaling arms, overexpression of constitutively active Rac-1 in muscle cells increases surface GLUT4 (23), although the molecular underpinnings are unknown. Here, we build on that observation and unravel the signaling mechanism.…”
mentioning
confidence: 99%
“…Activation of Akt stimulates the phosphorylation of its substrate protein (AS160) while Rac1 leads to the phosphorylation of p21 protein-activated kinase (PAK) (Manser et al, 1994). The cross talk in between Akt and Rac1 signaling cascades has already reported by some authors (Khayat et al, 2000;Ueda et al, 2008;Delaney et al, 2012;Chiu et al, 2013), as most studies describing the specific role of Akt and Rac1 in cytoskeletal rearrangement and glucose transport, have used mature skeletal muscle cells. Although, these are potent tools to understand the molecular mechanism in the mature skeletal muscle cells differ from cultured muscle cells in the face of various proteins and structural architecture that may influence the insulin response (Lauritzen et al, 2006;Tondeleir et al, 2009;Lauritzen and Schertzer, 2010).…”
Section: Discussionmentioning
confidence: 87%